In other words a comprehensibility assessment of lease agreements - Evangelista, Ma. Hazel D.; Lorenzo, Ann Margaret K. (College of Arts and Letters, University of the Philippines Diliman, 2010)
This research is an assessment of the comprehensibility of lease agreements in the Philippines. A lease agreement is an example of legal documents that frequently come in contact with people, and yet is also the prime evidence of convoluted use of language. Considering these, it becomes necessary to look into lease agreements and determine if laypeople still manage to understand perfectly what these texts seem to present before them. Using two lease agreements, one in traditional legalese found in the Philippines and the other a plain language version that exists in the United States, a comparative study for comprehensibility was done. The Logogen Model and the Derivational Theory of Complexity (DTC) were used to bridge the connection between language and cognition. These two theories were used to explain the results gathered from the questionnaires. This study proved that the plain language version approved by the PLM was indeed more comprehensible to the laymen when compared to the traditional legalese form. Therefore, this study advocates following recommendations of PLM and applying them to legal forms here in the Philippines. Doing so will help guarantee that people involving themselves in legal transactions really know they are involving themselves in.